2017
DOI: 10.3389/fncir.2017.00042
|View full text |Cite
|
Sign up to set email alerts
|

Trace Conditioning in Drosophila Induces Associative Plasticity in Mushroom Body Kenyon Cells and Dopaminergic Neurons

Abstract: Dopaminergic neurons (DANs) signal punishment and reward during associative learning. In mammals, DANs show associative plasticity that correlates with the discrepancy between predicted and actual reinforcement (prediction error) during classical conditioning. Also in insects, such as Drosophila, DANs show associative plasticity that is, however, less understood. Here, we study associative plasticity in DANs and their synaptic partners, the Kenyon cells (KCs) in the mushroom bodies (MBs), while training Drosop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 86 publications
3
45
0
Order By: Relevance
“…Below, we specify which model supports each prediction. (36) reported such decaying responses in DANs in the γ-and β -lobes during paired CS+ and US stimulation. However, they reported similar decaying responses when the CS+ and US were unpaired (separated by 90 seconds) that were not significantly different from the paired condition.…”
Section: Predictionsmentioning
confidence: 88%
See 1 more Smart Citation
“…Below, we specify which model supports each prediction. (36) reported such decaying responses in DANs in the γ-and β -lobes during paired CS+ and US stimulation. However, they reported similar decaying responses when the CS+ and US were unpaired (separated by 90 seconds) that were not significantly different from the paired condition.…”
Section: Predictionsmentioning
confidence: 88%
“…Ultimately, the evidence for either effect is insufficient. Moreover, Dylla et al (36) observed increases in DAN responses to the CS+ during training. This is consistent with the temporal difference learning algorithm (37; 38), which is an extension of the Rescorla-Wagner rule.…”
Section: Predictionsmentioning
confidence: 98%
“…7e). Such responses have been observed in modulatory neurons of species across the animal kingdom 12,23,32 , including adult and larval Drosophila 43,44,144 . They are consistent with a computa-tion of the valence of the US that is predicted by the CS+ (i.e.…”
Section: Feedback Neurons Enable Adaptive Responses Of Modulatory Neumentioning
confidence: 93%
“…Flies exhibit various olfactory associative behaviors that cannot be explained by the models presented here. For example, similar to other organisms, flies can form associations between stimuli that are not presented simultaneously, but instead presented in a predictable temporal order, a type of memory known as trace memory . Thus, flies can form associations between a CS and a US when the US is presented after termination of the CS.…”
Section: Perspectivesmentioning
confidence: 99%
“…For example, similar to other organisms, flies can form associations between stimuli that are not presented simultaneously, but instead presented in a predictable temporal order, a type of memory known as trace memory. [68][69][70] Thus, flies can form associations between a CS and a US when the US is presented after termination of the CS. This type of memory also requires the MBs, suggesting that the MBs maintain a CS memory trace in the absence of a US.…”
Section: Perspectivesmentioning
confidence: 99%